Analysis of Key Social and Economic Factors of Farmers Benefiting from Grants Provided by the Rural Economic Growth and Employment Project within Savings and Credit Groups in Jordan - Shammout, Amin Osama; Al-Nsour, Zaid Fahed; Abo Hammour, Mohammad AbdAlFattah (Journal of agricultural, environmental and veterinary sciences, 2025)
The study aimed to estimate the benefit derived from the grants provided by the Rural Economic Growth and Employment Project (REGEP) for savings and credit groups; evaluating the differences in the most prominent social and economic factors among farmers benefiting from the grants, including the achievement of grant objectives across various governorates; examining the impact of the grants on marketing practices through the adoption of electronic marketing techniques; and identifying the main challenges faced by beneficiary farmers in achieving the grants’ objectives. Non-parametric tests were employed as the primary analytical methodology due to the failure to meet the assumptions required for parametric tests. The sample consisted of 242 grants. The study’s key recommendations emphasized the need to intensify efforts in the governorates of Ma’an and Tafileh to enhance productivity and income levels, in comparison to other governorates such as Irbid, Ramtha, and Madaba, which showed higher increases in productivity and income among beneficiaries. This can be achieved by highlighting success stories and the supportive factors contributing to them. Additionally, the study recommended exploring sufficient funding mechanisms to meet grant objectives, as challenges in securing adequate funding were found to negatively impact productivity and income enhancement. Continuous support through free or volunteer-based advisory services provided by civil society organizations was also deemed crucial. In addition, the study also recommends re-examining ways to address the obstacles to farmers’ export capabilities.